Subclavian-coronary bypass graft re-operation according to the MICS technique in a patient with angina relapse - I. Yu. Sigaev; M. A. Keren; A. V. Kazaryan; I. V. Pilipenko; G. G. Getsadze (Российский кардиологический журнал)
Coronary artery bypass graft (CABG) using short-scar incision (without median sternotomy) allows minimizing the invasiveness of the intervention, reducing the risks of postoperative complications, and also ensuring patient comfort and quick social and physical rehabilitation. The successful implementation of such operations is due not only to surgical skills and the integration of technological achievements into practice, but also to the appropriate selection of patients. The article presents a clinical case of successful re-operation of the subclavian-coronary artery bypass grafting on a beating heart using antero-lateral thoracotomy approach in a patient with angina relapse after CABG.